Location and Welfare in Cities: Impacts of Policy Interventions on the Urban Poor - Kapoor, Mudit; Lall, Somik V.; Lundberg, Mattias K. A.; Shalizi, Zmarak (World Bank, Washington, D.C., 2013)
Informal settlements are an integral part of the urban landscape in developing countries. These settlements are widely distributed within cities, including central business centers and peripheral areas with environment hazards. In most cases, residents of these settlements do not have access to basic public services and amenities. In this paper, the authors examine the impact of interventions, such as upgrading basic services and resettlement policies, on the welfare of residents of these informal settlements, who are typically the urban poor. To examine these interventions, they estimate models of residential location choice and allow households to be sensitive to commuting costs to work, demand for public services, and preferences for community composition. The authors' empirical analysis is based on recently collected survey data from Pune, India, and shows that poor households prefer to live close to work and in communities that consist of people sharing common socio-demographic characteristics. From the perspective of households living in informal settlements, upgrading settlements in the original place is welfare enhancing. If a household must be relocated, it greatly prefers to be moved to a community that resembles its current community.